(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The rice husk ash is mixed with soil in various proportions like 5%, 10%, 20%, 30%, 40% & 50%. The different tests were conducted in order to determine the different characteristics and properties of the red soil and obtained with following results. The liquid limit of the soil with addition of rice husk ash was found to be decreasing when compared to liquid limit of soil alone. The plastic limit of the soil increased with the addition of rice husk ash. The MDD of the soil with addition of rice husk ash by weight of soil is found to be decreases and the corresponding OMC is increased with addition of rice husk ash.